Evaluation of biofilm removal and adverse effects on acrylic resin by diluted concentrations of sodium hypochlorite and Ricinus communis solutions. (23rd May 2018) - Arruda, Carolina N. F.; Salles, Marcela M.; Badaró, Maurício M.; Sorgini, Danilo B.; Oliveira, Viviane C.; Macedo, Ana P.; Silva‐Lovato, Cláudia H.; Paranhos, Helena F. O.
Abstract : Purpose: To verify whether 0.1% and 0.2% sodium hypochlorite (NaOCl), and 8% Ricinus communis (RC) were able to remove denture biofilm without causing deleterious effects to acrylic resin. Background: Previous data show that denture cleansers are effective in reducing biofilm; however, they can change acrylic resin properties. Methods: In a crossover trial, 47 denture wearers brushed and soaked their dentures (20 min/14 d): control, 0.85% saline; SH1, 0.1% NaOCl; SH2, 0.2% NaOCl and RC. Denture biofilm on the intaglio surface was stained, photographed and quantified (Image Tool ® ). Furthermore, 80 rectangular and 80 disc‐shaped specimens (Lucitone 550) were assigned into tested solutions (n = 20), simulating 5 years of daily short immersions (20 minutes). A colorimeter and the National Bureau of Standards units (NBS) determined colour data (ΔE). Surface roughness and flexural strength were measured using rugosimeter and universal testing machine, respectively. Data were compared by the Friedman test (α = .05) followed by Wilcoxon, corrected by Bonferroni (α = .005) (clinical) and Kruskal‐Wallis followed by the Dunn test (α = .05) (laboratorial). Results: SH2 (MR=1.77) showed lower biofilm coverage; SH1 (MR = 2.37) and RC (MR = 2.74) presented intermediated values. RC (1.10 [0.96:1.75]) revealed higher colour alteration than SH1 (0.71 [0.62:0.80]) and SH2 (0.74 [0.58:0.85]); however, NBS classified all solutions as "trace" (0.0‐0.5). There was no statistical significance for surface roughness ( P = .760) and flexural strength ( P = .547). Conclusions: The 0.2% NaOCl showed the best clinical performance and did not cause adverse effects on acrylic resin on laboratory analyses.